MUTU PELAYANAN KELUARGA BERENCANA DI INDONESIA - Saparinah Sadli (Populasi, 1997)
The quality of TP service in Indonesia stillshows some weak points i.e. weaknesses in the quality ofgimng information and in that of interpersonal interaction, so that the clients who want to optimally get their satisfaction in the choice of effective, economically reachable, safe, and suitable methods become vague. Saparinah Sadli, in her writing shows the weak points of the TP service based on an emperical study. Turther, she also shows the solution formula related to the Cairo action program.